Total laparoscopic versus laparoscopic-assisted transabdominal posterior mediastinal digestive tract reconstruction in the treatment of Siewert II adenocarcinoma of the esophagogastric junction: A retrospective study - Wang, Liang; Chen, Xiaoqian; Miao, Wei; Ma, Yubin; Ma, Xinfu; Wang, Chun; Cao, Xiaobo; Xu, Hongyin; Wei, Jiajia; Yan, Su (Frontiers in Surgery, 2022)
Background The method of operation and the range of resection for Siewert Ⅱ adenocarcinoma of the esophagogastric junction (AEG) remain controversial. This study aims to evaluate the safety, feasibility, and short-term postoperative effect of total laparoscopic versus laparoscopic assisted transabdominal posterior mediastinal digestive tract reconstruction in the treatment of Siewert Ⅱ AEG. Methods Total laparoscopic or laparoscopic assisted gastrointestinal reconstruction through abdominal posterior mediastinum was performed in 108 patients with Siewert Ⅱ AEG from October 2017 to February 2019. This study evaluated the loss of intraoperative blood, the number of lymph nodes, the marginal of tumor, short-term postoperative complications (within 30 days), the rate of survival at follow-up, and the economic cost, feasibility and effect of short-term postoperative recovery for patients who received these two operations. Result There were no significant differences in general data between total laparoscopic group and laparoscopic assisted group (P > 0.05). However, the total laparoscopic group costed more time on the surgical procedure and digestive tract reconstruction, lose less intraoperative blood, had more mediastinal lymph nodes compared with the laparoscopic assisted group (P < 0.05). The total laparoscopic group was significantly better than the laparoscopic assisted group compared with the short-term postoperative recovery indexes, such as the first exhaust time, the first defecation time, the first fluid time, the first semi-fluid diet time, the postoperative hospital stay and other postoperative recovery indexes (P < 0.05). In addition, there were no significant differences in postoperative complications, postoperative pathological indexes, the recurrence rate and mortality between the total laparoscopic group and laparoscopic assisted group (P > 0.05). Conclusions The safety, feasibility and short-term effect of total laparoscopic transabdominal posterior mediastinal digestive tract reconstruction in the treatment of Siewert Ⅱ AEG were better than the laparoscopic assisted group.